2004
DOI: 10.1046/j.1439-037x.2003.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Dry‐Matter Production, Allocation and Nutritive Value of Forage Chicory Cultivars as a Function of Nitrogen

Abstract: Forage chicory cultivars vary in origin and morphology and may respond differently to nutrient inputs because of photosynthate allocation and resource acquisition. Understanding nitrogen (N) influences on chicory seedling development and allocation of photosynthates among plant parts is important in terms of stand establishment, plant persistence, herbage production and nutritive value. We conducted experiments in the glasshouse to determine if amount (0, 50 and 100 mg N kg−1 soil) and source (ammonium nitrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…At this time, increasing N inputs from 180 kg N/ha/year to 450 kg N/ha/year increased the CP concentration of ryegrass, chicory and plantain by an average of 3.2 g CP/kg DM. Chicory and plantain at low N inputs in summer had a higher average CP concentration (153 g CP/kg DM) than ryegrass (119 g CP/kg DM), which is consistent with the results of previous studies (Sanderson et al 2003;Belesky et al 2004). Where N fertiliser use is limited herbs may provide a suitable alternative to meet CP requirements.…”
Section: Fibresupporting
confidence: 90%
“…At this time, increasing N inputs from 180 kg N/ha/year to 450 kg N/ha/year increased the CP concentration of ryegrass, chicory and plantain by an average of 3.2 g CP/kg DM. Chicory and plantain at low N inputs in summer had a higher average CP concentration (153 g CP/kg DM) than ryegrass (119 g CP/kg DM), which is consistent with the results of previous studies (Sanderson et al 2003;Belesky et al 2004). Where N fertiliser use is limited herbs may provide a suitable alternative to meet CP requirements.…”
Section: Fibresupporting
confidence: 90%
“…In these circumstances, the use of alternative forage species has been considered to increase forage production during the summer. Crops such as chicory and English plantain have been tested for this purpose (Jung et al, 1996; Holden et al, 2000; Foster et al, 2002; Sanderson et al, 2003a, 2003b; Belesky et al, 2000, 2001, and 2004). Research suggests that forage chicory can complement and even improve seasonal dry matter (DM) productivity of pastures in the northeastern USA (Sanderson et al, 2003a; Labreveux et al, 2004), where, aside from alfalfa, species such as orchardgrass and reed canarygrass predominate due to their summer yields.…”
mentioning
confidence: 99%
“…Hogh‐Jensen et al (2006) found that chicory competed strongly for soil mineral N when included in perennial ryegrass‐legume mixtures. Given the superior ability of chicory to scavenge soil N (Belesky et al, 2004; Hogh‐Jensen et al, 2006) it is expected that the majority of fixed N subsequently released from any companion legumes would be accumulated in the chicory plant residues. Therefore, it is important to understand the release of N accumulated in chicory plant residues into the soil via N mineralisation.…”
Section: Introductionmentioning
confidence: 99%